The Use of Series Image Media to Improve the Ability to Write Non-Fiction Text - Risdiyati, Fatma (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research is to improve the ability to write non-fiction texts. This research is a classroom action research (PTK) which is conducted in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fifth grade students of SD Negeri 2 Bodaskarangjati for the 2020/2021 academic year, totaling 15 students. Data collection techniques using observation, interviews, data analysis, and tests. The data analysis technique used in this study is a comparative descriptive analysis technique, which is to compare the results of each cycle's actions with the predetermined work indicators. Interactive analysis is the interaction of the four components developed by Milles and Huberman (in H.B Sutopo, 2002: 96). The four components are 1) data collection, 2) data reduction, 3) data presentation in an effort to display data clearly and easily understood in narrative exposure, graphics, or other forms, and 4) drawing conclusions. Research shows that the use of serial image media can improve the ability to write non-fiction text in class V SD Negeri 2 Bodaskarangjati in the 2020/2021 school year as evidenced by the percentage of completeness of learning outcomes in cycle I by 40% to 93% in cycle III.